How does ethical leadership trickle down? Test of an integrative dual-process model - Wang, Z.; Xu, H.; Liu, Yukun (Springer Netherlands, 2016)
Although the trickle-down effect of ethical leadership has been documented in the literature, its underlying mechanism still remains largely unclear. To address this gap, we develop a cross-level dual-process model to explain how the effect occurs. Drawing on social learning theory, we hypothesize that the ethical leadership of high-level managers could cascade to middle-level supervisors via its impact on middle-level supervisors’ two ethical expectations. Using a sample of 69 middle-level supervisors and 381 subordinates across 69 sub-branches from a large banking firm in China, we found that middle-level supervisors’ ethical efficacy expectation and unethical behavior–punishment expectation (as one form of ethical outcome expectations) accounted for the trickle-down effect. The explanatory role of middle-level supervisors’ ethical behavior–reward expectation (as the other form of ethical outcome expectations), however, was not supported. The theoretical and practical implications are discussed.